The Impact of Career Calling on Economics Students’ Learning Engagement: The Mediating of Career Commitment - Arisa Jelita Putri; Yuki Fitria (Universitas Negeri Padang, 2024)
This research investigates the impact of career calling on students' learning engagement, taking into account the mediating role of career commitment. The research participants consisted of 213 students selected through cluster random sampling techniques from various economics majors. Data analysis was carried out using Structural Equation Modeling (SEM), with data processing using Partial Least Square (PLS). The results of the hypothesis test show that career calling has a positive effect on learning engagement. Apart from that, career commitments also influence learning engagement. From the test results it can also be proven that career commitment is able to mediate the relationship between career calling and learning engagement of economics students at Padang State University. These findings highlight the importance of increasing learning engagement among students to carefully design learning activities for their future career development.